Angular dependence of Raman spectrum for Pb(Zr, Ti)O3 epitaxial films. (15th September 2016) - Fukushima, Hiroaki; Ichinose, Daichi; Funakubo, Hiroshi; Uchida, Hiroshi; Shima, Hiromi; Nishida, Ken
Abstract: Herein, we investigate the angular dependence of the Raman spectra of (001)/(100)-oriented tetragonal and (111)/ -oriented rhombohedral epitaxial lead zirconate titanate (PZT) films. The A 1 and E modes have the same angular dependence for the (111)/ -oriented rhombohedral epitaxial PZT film, but not for the (001)/(100)-oriented tetragonal epitaxial PZT film. These results agree well with theoretical predictions. On the basis of the fact that the angular dependence of the phonon mode in PZT films is linked to the crystal orientation and structure, the angular dependence of the Raman modes can be used to investigate the orientation and structure of PZT films.